Design and Implementation of an Innovative Torch Rotary Welding Special Purpose Machine (SPM) for Enhanced Welding Precision and Efficiency - Wandel, A.A. (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
Robots are frequently utilised in industrial welding processes in addition to the logical technical process. The welding process is sophisticated and not well understood, and human-machine interfaces are unnatural and ineffective. Another issue with robots is that they are still in the early stages of development and challenging for regular operators to use and programme. Welding is a joining or manufacturing procedure that joins materials—usually metals or thermoplastics—by melting the base metal with the filler. The automated Torch Rotary soldering machine's design was influenced by gas metal arc welding.Automation helps to save expenses and increase system productivity. Flash welding has been done automatically. In our assignment, we must weld two circular welding spots into an automotive component. Manual welding uses more personnel and results in worse production and welding quality, among other things. By using automatic welding, all of the aforementioned issues are resolved, and manual welding enhances the system as a whole. The GMAW procedure is utilised using a torch on a torch rotary machine to weld the exhaust system. For this action, the machine has a fixture. During welding, the welding torch revolves around the pipe and flange.